The effect of economic crisis and austerity measures on deaths of despair in Brazil: An interrupted time series analysis. - Raphael Mendonça Guimarães; Karina Cardoso Meira; Cristiane Teixeira da Silva Vicente; Silvania Suely de Araújo Caribé; Luise Bernardes da Silva Neves; Nicole Almeida Vardiero (PLoS ONE)
Some recent analyses have described that, in the context of the instability of social protection institutions and economic crisis, there is an increase in mortality rates selectively from drug overdoses, suicides and alcohol-related liver diseases. This group of causes was named "Deaths of Despair. In the last decade, Brazil experienced economic stagnation and fiscal austerity, influencing the profile of illnesses and deaths. Therefore, our study aimed to evaluate the effect of the economic crisis and fiscal austerity measures on deaths of despair in Brazil and to describe the trend of deaths of despair in Brazil between 2003 and 2018, according to the phases of the economic cycle. We analyzed the time series of rates by covariates and fitted an interrupted time series model to assess the effect of the crisis on the trend through the Prais-Winsten method. The temporal analysis showed a significant difference in the mean values ​ before and after economic stagnation (Mean 8.68 ± 0.71) and after (Mean 11.62 ± 0.62). We found a positive association between the economic crisis and deaths of despair, with a significant change in level (p-value = 0.003) and a non-significant trend effect (p-value = 0.300). There are differences in sex, age, and especially race: men, middle-aged and black/brown people are more at risk. The present study presents the effect of the economic crisis and mortality in the population, with demographic differences.